Sustainability of smallholder oil palm plantations: A study in Riau, Indonesia - Hartinah, Siti; Darwanto, Dwidjono Hadi; Suryantiny, Any; Utami, Arini Wahyu (Edelweiss Applied Science and Technology, 2025)
Oil palm plantation is a strategic commodity for the national economy and the welfare of communities. Smallholder oil palm plantations, as part of the palm oil supply chain, are facing sustainability matters. This study aims to assess the index and status of sustainability across the social, economic, environmental, technological, and institutional dimensions, as well as identify sensitive attributes affecting the sustainability of smallholder oil palm plantations. The index assessment utilized the RAP-ISPO method through MDS. The MDS analysis covers all of the aforementioned dimensions. The study was conducted in two major oil palm plantation sub-districts in Riau Province, including Dayun and Mempura. This study used both primary and secondary data. Primary data were gathered through interviews, surveys, and observations. Secondary data were sourced from relevant agencies such as the Central Statistics Agency, Siak Agricultural Office, and related research articles or reports. The respondents were 203 farmers, who were selected purposively. The multidimensional sustainability index analysis of oil palm plantations in Riau has yielded an overall sustainability index of 63.30, which falls into the "sufficiently sustainable" category. The sustainability indices for the five dimensions are as follows: economic (60.85%), social (67.54%), environmental (53.91%), technological (71.70%), and institutional (62.51%). The technological dimension has the highest index value, while the environmental dimension has the lowest. Overall, each dimension falls into the "sufficiently sustainable" category, with varying index values, indicating the need for different policies to evaluate the sustainability of smallholder oil palm plantations in Riau.